THE FIRST HEAD OF STATE FOR SARAWAK: THE NATIVE OFFICERS’ CONNECTION - Sharifah Sophia, Wan Ahmad; Juna, Liau; Dexter Sigan, John (UNIVERSITI SAINS MALAYSIA, 2025)
The key personalities at the forefront of the debate about the nomination for the first Head of State for Sarawak, which took place from January to September 1963, were Chief Minister Stephen Kalong Ningkan, Malayan Prime Minister Tunku Abdul Rahman al-Haj, and the last British Governor of Sarawak, Sir Alexander Waddell. This was a controversy because of the lack of consensus within the parties that formed the Sarawak Alliance and became exacerbated by prolonged disagreements between Ningkan, Tunku and Waddell until its resolution was found three days before the official pronouncement of Malaysia on 16 September 1963. The perspectives of these leading players thus far constitute a standardised account about the debate, admittedly, with varying degrees of emphasis and competing claims. This study proposed another perspective another perspective on the debate by introducing the role of the Native Officers who worked behind the political gallery. They were the unsung heroes working for the cause of federation, subsequently clearing the ground for the eventual triumph of their class. By unravelling the Native Officers’ role in the formation of Malaysia, we demonstrate the administrator’s important as a continuing source of political stability and moderation. To appraise the administrator’s dimension in the modern history of Malaysia serves as a lesson on political tolerance and compromise in the context of a multi-ethnic society.